Fatigue Crack Growth Detect - Assess - Avoid - Richard, Hans Albert; Sander, Manuela; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book offers a concise introduction to fatigue crack growth, based on practical examples. It discusses the essential concepts of fracture mechanics, fatigue crack growth under constant and variable amplitude loading and the determination of the fracture-mechanical material parameters. The book also introduces the analytical and numerical simulation of fatigue crack growth as well as crack initiation. It concludes with a detailed description of several practical case studies and some exercises. The target group includes graduate students, researchers at universities and practicing engineers.
Preface -- 1 Designing Components and Structures According to Strength Criteria -- 2 Damages Caused by Crack Growth -- 3 Fundamentals of Fracture Mechanics -- 4 Fatigue Crack Growth under Cyclic Loading with Constant Amplitude -- 5 Experimental Determination of Fracture-Mechanical Material Parameters -- 6 Fatigue Crack Growth under Service Loads -- 7 Simulations of Fatigue Crack Growth -- 8 Crack Initiation under Cyclic Loading -- 9 Practical Examples -- 10 Important Symbols -- Index.
Keywords: Mechanical engineering; Building materials; Mechanics, Applied; Solids; Mechanical Engineering; Structural Materials; Solid Mechanics